Implementation of an Informatics-Based QMS Dashboard in the Campus Environment - Deitje Sofie Pongoh; Noel Abraham Tjandra Tampi; Rifly Nesta William Tijow; Ikhsan Praditya Mokosolang; Vindri Laudya Runtuwene (Publikasi Indonesia, 2026)
The implementation of a Quality Management System (QMS) in higher education institutions is an essential step to ensure the quality of education, research, community service, and administrative governance. However, QMS processes that are still carried out manually often create barriers such as delays in reporting, scattered data, and limited transparency. This study aims to design and implement an informatics-based QMS Dashboard as a solution for integrating quality data within higher education institutions. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observations, interviews, and questionnaires involving 120 respondents from the academic community. The system was designed as a web-based application using the Laravel framework, MySQL database, and Chart.js for interactive data visualization. The findings show that the QMS Dashboard significantly improves the efficiency of quality management. Accreditation report preparation time decreased by up to 40%, user satisfaction reached 87%, and the effectiveness of quality evaluation increased substantially. Respondents stated that the system excels in accessibility, transparency, and data integration. Thus, the implementation of an informatics-based QMS Dashboard has proven effective in strengthening quality culture, enhancing transparency, and expediting decision-making processes in higher education. This system can serve as a reference for other institutions to support digital transformation in educational quality assurance systems.